Anterior cruciate ligament abnormalities are associated with accelerated progression of knee joint degeneration in knees with and without structural knee joint abnormalities: 96-month data from the Osteoarthritis Initiative. Issue 7 (July 2021) - Gersing, A.S.; Schwaiger, B.J.; Nevitt, M.C.; Joseph, G.B.; Feuerriegel, G.; Jungmann, P.M.; Guimaraes, J.B.; Facchetti, L.; McCulloch, C.E.; Makowski, M.R.; Link, T.M.
Summary: OBJECTIVE: To compare progression over 8 years in knee compositional cartilage degeneration and structural joint abnormalities in knees with different types of anterior cruciate ligament (ACL) abnormalities over 8 years. Method: Baseline MR images of the right knees of 1899 individuals of the Osteoarthritis Initiative (OAI) with no evidence of or mild to moderate radiographic osteoarthritis were assessed for nontraumatic ACL abnormalities. The knees of 91 individuals showed nontraumatic ACL abnormalities (age 60.6 ± 9.8 y, 46 females; mucoid degeneration (MD), N = 37; complete tear (CT), N = 22; partial tear (PT), N = 32) and were frequency-matched to 91 individuals with normal ACL. MRIs were assessed for knee joint abnormalities using the Whole-Organ Magnetic Resonance Imaging Score (WORMS) and cartilage T2 mapping at baseline, 4- and 8-year follow-up. Results: Over 8 years, cartilage T2 values of the medial tibia showed a significantly greater increase in individuals with MD, PT or CT compared to those with normal ACL (adjusted rate of change/year [95% confidence interval], normal ACL: 0.06 [0.01, 0.23], MD: 0.34 [0.07, 0.73], PT, 0.21 [0.02, 0.33], CT, 0.51 [0.16, 0.78]), indicating an association of ACL abnormalities and an increased progression rate of cartilage degeneration in subjects with and without knee joint degeneration. This effect was also seen in cartilage T2 values averaged over all compartments (normal ACL: 0.08 [0.05, 0.20] vs abnormal ACL: 0.27 [0.06, 0.56]). Conclusions: Over 8 years, higher progression rates of cartilage degeneration, especially in the medial tibia, were associated with ACL abnormalities compared to those with normal ACL, in subjects with and without knee joint abnormalities.